Blockade of CD40/CD40 Ligand Interactions Prevents Induction of Factor VIII Inhibitors in Hemophilic Mice but Does not Induce Lasting Immune Tolerance - Reipert, Birgit M.; Sasgary, Maria; Ahmad, Rafi U.; Turecek, Peter L.; Schwarz, Hans Peter (Thrombosis and Haemostasis, 2001)
Patients with severe hemophilia A frequently develop neutralizing anti-factor VIII antibodies after replacement therapy with factor VIII (FVIII). In a search for new strategies to induce immune tolerance against FVIII in these patients, we used a murine model of hemophilia A to investigate the importance of CD40/CD40 ligand (CD40L) interactions for the initiation of the anti-FVIII immune response. We focused our attention in particular on the induction of neutralizing anti-FVIII antibodies and the Th1/Th2 polarization of FVIII-specific T cells. The development of anti-FVIII antibodies was analyzed by ELISA systems (detection of total anti-FVIII antibodies) and Bethesda assays (determination of neutralizing anti-FVIII antibodies). Factor VIII-specific T cells were characterized by multiparameter flow cytometry and cytokine ELISAs for the detection of cytokine production in splenic CD4+ T cells after in vitro restimulation with FVIII. Hemophilic mice received four doses of FVIII and anti-CD40L antibody MR1 (24 h before FVIII). Subsequently mice received four doses of FVIII only. The induction of neutralizing anti-FVIII antibodies in hemophilic mice after treatment with human FVIII could be prevented completely by a blockade of CD40/CD40L interactions using MR1. Furthermore, FVIII-specific T-cell responses that included both Th1 and Th2 cells were suppressed when mice were treated with FVIII and MR1. The initial blockade of CD40/CD40L interactions was, however, not sufficient to induce a lasting immune tolerance against FVIII. The immune suppression was abolished and both neutralizing anti-FVIII antibodies and FVIII-specific T cells developed when treatment with FVIII was continued after the omission of MR1. In addition, there were no alterations in the Th1/Th2 polarization induced by the initial blockade of CD40/CD40L interactions.
Keywords: Hemophilia A; factor VIII inhibitors; T cells; immune tolerance; CD40 ligand